Global value chains and unequal exchange: Market power and monopoly power - Deepankar Basu; Ramaa Vasudevan (University of Massachusetts, Department of Economics, 2021)
We revisit the hypotheses of unequal exchange and deterioratingterms of trade in the specific context of import-intensive, export-led strategies of developing countries which rely on integration intoGVCs for access to markets in developed countries using a stylizedtwo-country two-commodity Classical- Marxian trade model. Twosources of asymmetry can be distinguished: market power arisingfrom the competition between suppliers that depresses the prices atwhich the final good is supplied; and monopoly power arising fromthe lead firms control and ownership of intangible assets includingbrand and design. The model explores some implications of thesetwo sources of asymmetry.
Keywords: F02; F23; O19; 330; Unequal Exchange; Global Value Chains; Classical TradeModel